Eponymous Names in Acne - Shekhar K.C. (Nepal Journal of Dermatology, Venereology & Leprology)
Numerous terminologies have been linked to acne and related lesions which often puzzles students and practitioners. Here we have tried to summarize some of the common acne related terms found in related literatures.